Propuesta de mejoramiento de la productividad de procesos constructivos en proyectos de la empresa Volio y Trejos - Salas-Boza, Juan Manuel (Instituto Tecnológico de Costa Rica, 2018)
The topic developed consists in the improvement of productivity of construction processes in the projects, CEDI Coris and iFreses developed by Volio y Trejos Asociados construction company, through an improvement plan that suggests good practices. The processes analyzed are masonry block placement, cell filling, formwork, casting and demoulding of columns, and formwork and demoulding of slabs with Forsa and Conventional systems. For this, it was necessary to measure the productivity and yields, by techniques such as Crew Balance. The activity that had the greater efficiency was the masonry, and the one of lower productivity was the formwork and demoulding of slabs. Waiting, transportation, site design and oversizing of crews were identified as causes of decreased efficiency, by methods such as surveys, Ishikawa diagrams and expert queries. Likewise, the use of GPS watches was implemented in the collaborators as a tool to know the routes they were taking. With these data, an improvement plan was designed, composed of recommendations, which were gradually implemented. It was concluded that it was possible to improve productivity in CEDI Coris, but it could not be verified in iFreses, due to the lack of implementation.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2018.
Keywords: Mejoramiento; Productividad; Procesos; CEDI; Redimiento; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture::Building engineering